Barriers and challenges: a descriptive qualitative study of job satisfaction among direct care workers who provide long-term care services in Shandong Province, China - Qiang Sun; Jia Yin; Jing Gao (BMJ Open, 2025)
Background The special nature of the functional ability of older individuals with disabilities places higher demands on the quantity and quality of long-term care (LTC) services. However, LTC services lag significantly behind, with LTC facilities facing challenges in recruiting and retaining direct care workers (DCWs). Job satisfaction significantly affects turnover rates. To enhance the stability of the care workforce, there is an urgent need for an in-depth analysis of the barriers and challenges that affect job satisfaction from the perspective of DCWs.Objectives This study uses the Herzberg’s two-factor theory to explore the barriers and challenges that affect job satisfaction among DCWs in LTC services from their perspective.Design A descriptive qualitative study design involving face-to-face semistructured interviews. Thematic framework analysis was used to generate qualitative codes and identify themes.Participants The study included 31 DCWs from an LTC service institution.Setting This study was conducted in Shandong Province, China. In each city, 3–4 medium-sized to large-sized facilities that provided LTC care services were selected.Results DCWs faced barriers in terms of motivation and hygiene factors. The hygiene factors deficiencies are primarily related to systemic barriers to LTCI policy and the absence of a home care safety system. The main impediments to motivational factors include poor working conditions, discordant interpersonal communication, emotional labour overload and low occupational identity.Conclusions DCWs face multiple barriers and challenges related to job satisfaction. This study may provide a framework to guide the improvement of intervening variables in the provision of LTC services. In the future, more emphasis should be placed on service providers as the mainstay of LTC policy practice; this will ensure that both the hygiene and motivation factors among DCWs are addressed and implemented simultaneously. Concurrently, the LTC insurance system should be used as a guarantee to promote the synergistic development of LTC services and the stability of the DCWs.